Oil and gas energy potential at Malaysian seabed and spar platform for deepwater installation - Islam, A.B.M.S.; Jameel, M.; Jumaat, Mohd Zamin (Taylor & Francis, 2012)
Offshore sedimentary basins of Malaysian region indicate abundant sources of energy at its seabed. Furthermore, depletion of oil and gas reserves in its onshore land and shallow water depth has accelerated the exploration toward these deeper waters. Frequent increasing demand requires precise investigation to acquire these energies in optimum custom. A competent exploration structure is also desired for energy extraction from the deep water. In this study, oil and gas status in Malaysian scenario is reconnoitered. As the sea wave influences greatly on offshore structures, approaches for collecting wave data are sightseen. The structural configuration and characteristics of compliant floating spar platform for energy extraction are addressed. The study reveals that the continental shelf offshore of Malaysian waters is divided into seven sedimentary basins, among which three basins have major ongoing oil and gas extraction activity. Around 68 oil and 86 natural gas of the country's reserves are located in East Malaysia at offshore Sabah and Sarawak. Except the Kebabangan field, all the other offshore energy reserves are located at more than 1000 m depth. In lieu of a fixed platform, a floating platform will be a competent energy extraction structure in this deeper water. The deep water wave data can be appropriately obtained in satellite altimetry approach for its extent of accuracy. The first installed spar at Kikeh field denotes bright possibilities of incorporating spar platform in Malaysian sedimentary basins. If spar platforms are installed at these deeper vicinities, all the basins will certainly climb in optimum operation yielding a huge usable energy.